Construction of 2D TiO2@MoS2 Heterojunction Nanosheets for Efficient Toluene Gas Detection - Dehui Wang; Jinwu Hu; Hui Xu; Ding Wang; Guisheng Li (Chemosensors)
Monitoring trace toluene exposure is critical for early-stage lung cancer screening via breath analysis, yet conventional chemiresistive sensors face fundamental limitations, including compromised selectivity in complex VOC matrices and humidity-induced signal drift, with prevailing p–n heterojunction architectures suffering from inherent charge recombination and environmental instability. Herein, we pioneer a 2D core–shell n–n heterojunction strategy through rational design of TiO2@MoS2 heterostructures, where vertically aligned MoS2 nanosheets are epitaxially grown on 2D TiO2 derived from graphene-templated synthesis, creating built-in electric fields at the heterojunction interface that dramatically enhance charge carrier separation efficiency. At 240 °C, the TiO2@MoS2 sensor exhibits a superior response (Ra/Rg = 9.8 to 10 ppm toluene), outperforming MoS2 (Ra/Rg = 2.8). Additionally, the sensor demonstrates rapid response/recovery kinetics (9 s/16 s), a low detection limit (50 ppb), and excellent selectivity against interfering gases and moisture. The enhanced performance is attributed to unidirectional electron transfer (TiO2 → MoS2) without hole recombination losses, methyl-specific adsorption through TiO2 oxygen vacancy alignment, and steric exclusion of non-target VOCs via size-selective MoS2 interlayers. This work establishes a transformative paradigm in gas sensor design by leveraging n–n heterojunction physics and 2D core–shell synergy, overcoming long-standing limitations of conventional architectures.